Effect of Under Surface Cooling in Friction Stir Processing of Aluminum Alloy 6082: A Review - Singh, Harvinder; Singh, Rajdeep (Asian Review of Mechanical Engineering, 2018)
Friction Stir processing (FSP) is a new technique of Friction Welding. This technology is used in automobile and aerospace industries because it reduces the defects produces by conventional fusion welding techniques. Now in days Friction Stir Processing is introduced as a new process for microstructural surface modification of various materials or for changing the properties of metal by producing intense localized plastic deformation in the material. The main principle of this technique is based on FSW. The tool pin plunged in the plate and plastic deformation is produced by heat is generated due to rotational motion of too. Cooling of specimen during FSP is also a new research to improve the mechanical properties of base metal. The present investigation shows the effect of cooling of specimen on mechanical properties during FSP. It has been observed from this review paper that the effect of cooling of specimen greatly affected the mechanical properties of metal as compared to dry conditions. It has been observed that the values of yield strength and micro hardness increases in cooled region of welded joint.